TRANSAKSI REKAYASA PAJAK PADA TRANSFER PRICING MENURUT HUKUM ISLAM - Ria Achmadiyah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2014)
This article is the result of the research literature to answer how the mechanism of engineering transactions tax, how engineered transactions tax mechanism on transfer pricing, and how hukun Islamic perspective on engineering transaction tax on transfer pricing. Get an overview of research results that engineering transactions tax on transfer pricing is done by diverting profits of a company in a high tax cost countries to company branches located in low-tax countries cost (tax-haven) through transfer pricing. One of them with the sale or purchase at a price different from the market price, so the taxes paid into smaller ones. As a result of state income tax sector to be reduced. Transfer pricing transaction was actually done when intended for legitimate non-tax motive, namely to control the management, control of the market, and so on, because when viewed from the pillars and trading terms, transfer pricing transactions already comply. The research concludes that a transaction tax on the transfer pricing engineering in Islamic law considered acts perspetif za>lim although in substance transfer pricing transactions classified as a legitimate purchase. Further to the company in Indonesia, which has branches abroad or in tax-haven countries in order to run their business properly and honestly, including by paying taxes according to the amount of the obligations, because the tax is needed to fund the construction.